2019
DOI: 10.17921/2447-8733.2019v20n3p319-326
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficácia em Professores do Ensino Superior

Abstract: O objetivo deste estudo foi avaliar a percepção de autoeficácia em professores do Ensino Superior e avaliar as propriedades psicométricas da Escala de Autoeficácia para Professores do Ensino Superior para o contexto brasileiro. Participaram deste estudo 188 professores do Ensino Superior de instituições da rede privada de Minas Gerais. Os professores lecionavam nas áreas da Educação Física, Nutrição, Ciências Biológicas, Geografia, Fisioterapia, Medicina, Análise de Sistemas, Enfermagem, Turismo e Pedagogia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…At the national level, other studies that used the same instruments as this study, showed a tendency towards medium and, often, high levels of teacher self-efficacy among higher education teachers 27,35,38 . The hypotheses that justify the fact that the teaching group of the present study obtained a more median level of self-efficacy must be confirmed with new studies and qualitative analyses, which will address the specificities of medical teaching and with the use of techniques such as the OSCE.…”
Section: Discussionsupporting
confidence: 67%
“…At the national level, other studies that used the same instruments as this study, showed a tendency towards medium and, often, high levels of teacher self-efficacy among higher education teachers 27,35,38 . The hypotheses that justify the fact that the teaching group of the present study obtained a more median level of self-efficacy must be confirmed with new studies and qualitative analyses, which will address the specificities of medical teaching and with the use of techniques such as the OSCE.…”
Section: Discussionsupporting
confidence: 67%